Microbiology : an introduction - Tortora, Gerard J.; Funke, Berdell R.; Case, Christine L. (Menlo Park, Calif. : Benjamin/Cummings Pub. Co., 1982)
This book is a comprehensive text for students in a wide variety of programs, including allied-health sciences, biological sciences, environmental studies, animal science, forestry, agriculture, home economics and liberal arts.
Part I. Fundamentals of microbiology -- Part II. Survey of the microbial world -- Part III. Interaction of microbe and host -- Part IV. Microorganisms and human disease -- Part V. Microbiology, the environment, and human affairs.
Includes bibliographical references and index.
Keywords: MICROBIOLOGY